2011
DOI: 10.1371/journal.pone.0021535
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the HIV-1 env Genetic Context outside HR1–HR2 on Resistance to the Fusion Inhibitor Enfuvirtide and Viral Infectivity in Clinical Isolates

Abstract: Resistance mutations to the HIV-1 fusion inhibitor enfuvirtide emerge mainly within the drug's target region, HR1, and compensatory mutations have been described within HR2. The surrounding envelope (env) genetic context might also contribute to resistance, although to what extent and through which determinants remains elusive. To quantify the direct role of the env context in resistance to enfuvirtide and in viral infectivity, we compared enfuvirtide susceptibility and infectivity of recombinant viral pairs h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 54 publications
(85 reference statements)
0
16
0
Order By: Relevance
“…[6] Geno2pheno and WebPSSM are the most widely used among genotypic assays. Although clinical evidences provide support for the validity of using an FPR between 5% and 10% when applying Geno2pheno to predict subtype B tropism, [3335] several studies indicated that both Geno2pheno (FPR = 10%) and WebPSSM overestimates the presence of X4 viruses for CRF01_AE. [17,18] In this study, we adopted the recently published algorithm that uses combination of Geno2pheno (FPR = 10%) and WebPSSM to predict HIV-1 tropism.…”
Section: Discussionmentioning
confidence: 99%
“…[6] Geno2pheno and WebPSSM are the most widely used among genotypic assays. Although clinical evidences provide support for the validity of using an FPR between 5% and 10% when applying Geno2pheno to predict subtype B tropism, [3335] several studies indicated that both Geno2pheno (FPR = 10%) and WebPSSM overestimates the presence of X4 viruses for CRF01_AE. [17,18] In this study, we adopted the recently published algorithm that uses combination of Geno2pheno (FPR = 10%) and WebPSSM to predict HIV-1 tropism.…”
Section: Discussionmentioning
confidence: 99%
“…Viral cDNA was synthesized in a one-step RT-PCR reaction using forward primer KVL008 and reverse primer KVL009 [48] in 50 µl mix containing 5 µl viral RNA, 20 µM of each primer, 1 µl SuperScript III One-Step RT-PCR with Platinum Taq High Fidelity mix and 8 units RNAseOUT (all from Invitrogen, Merelbeke, Belgium) under the following conditions: initial denaturation at 94°C for 2 mins and 40 amplification cycles (94°C for 15 s, 60°C for 30 s, 68°C for 4 mins) followed by a final 10 mins extension step at 68°C. 2 µl of the amplified cDNA was further amplified using forward primer MM1 FP (5′-GCCTTAGGCATCTCTTATGGCAGGAAGAAG-3′) and reverse primer rec HR1-2_RP (5′-CTCTCTCTfCCACCTTCTTCTTC-3′) [27] in a 50 µl reaction mix containing 2 mM MgSO 4 , 0.2 mM of each dNTP, 20 µM of each primer, 2.5 Units Platinum Taq High Fidelity DNA polymerase. The amplification conditions were: initial denaturation step at 95°C for 3 min, 35 cycles of denaturation at 95°C for 30 s, annealing at 48°C for 30 s, extension at 68°C for 3 min, and a final extension step at 68°C for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…LTS-2 is a viremic controller [6][7][8] infected in 1992 and harboring an R5 provirus at the time of sampling (2006). Plasma neutralizing properties were confirmed in five longitudinal samples from 2006 to 2013 using a single cycle infection assay based on luciferase-tagged recombinant viral particles (RVA) [20,21]. LTS-2 genotyping revealed the absence of the CCR5 delta 32 deletion, the CCR2 V64I and the SDF1 G801A polymorphisms and combination of HLA A Ã 02/ Ã 11, B Ã 27/ Ã 35, and C Ã 02/ Ã 04 alleles.…”
mentioning
confidence: 92%